Ver-o-autismo: protótipo de aplicativo educacional sobre Transtorno do Espectro do Autismo para estudantes de Psicologia - SILVA, Rosine Lima (Universidade Federal do Pará, 2024)
The aim of this work is to develop Ver-o-autismo, a prototype of a mobile application for psychology students in training, who undertake clinical internship as part of their curriculum or extracurricular activities, with the intention of enhancing their skills in understanding and intervening in the context of Autism Spectrum Disorder.. To achieve the defined objective, the work was divided into three phases: 1) In the first phase, a literature review was conducted on the use of mobile technologies as a teaching-learning tool, the use of microlearning as a methodological proposal for the development of Ver-o-autismo application content, key concepts related to Autism Spectrum Disorder, and psychologist training in Brazil within this context; 2) The methodological path for the application's construction was then outlined, including the development of microcontent based on cues described by Buchem and Hamelmann (2010). Prototyping was carried out on the Figma platform, and tool development was implemented on the Android Studio platform version Flamingo 2022.2.1.20, using Java and HyperText Markup Language (HTML). Two requirements surveys were conducted through a Google Forms questionnaire to map the audience's interests and a review of related products on the Google Play Store to evaluate features of other existing applications on the subject; 3) In the final phase, the achieved results and their analysis were described, presenting the product and its main screens, along with its evaluation by six judges using the Learning Object Review Instrument (LORI) scale created and validated by Nesbit, Belfer, and Leacock (2009). Judges were selected from two specific groups, internship supervisors, and psychology students. The evaluation results demonstrate that the Ver-o-autismo application has the potential to fulfill the proposed objective. In the review of related products, no other applications with similar objectives to those developed in this work were found. This reinforces the uniqueness of the Ver-o-autismo application and its potential for innovation in Higher Education. Identified limitations are related to the scarcity of content focused on the diagnosis and intervention in adults and the elderly. In the presented perspective, it is believed that Ver-o-autismo has formative potential and offers significant contributions to the training of psychologists interested in working with individuals with autism. Thus, it provides an opportunity for a more committed and qualified involvement in this field.